Hangman - Kellerman, Faye (New York : William Morrow, 2010)
LAPD Lieutenant Peter Decker reluctantly agrees to do a big favor for an old friend, Teresa McLaughlin, but when she and her husband disappear, Decker's search is interrupted by the suspicious death of a young health care worker.
Keywords: Decker, Peter (Fictitious character) -- Fiction; Lazarus, Rina (Fictitious character) -- Fiction; Police -- Fiction -- California; Missing persons -- Fiction; Mystery fiction